The Effect of Independent Commissioners, Corporate Social Responsibility, Investment Decisions, Institutional Ownership and Funding Decisions on Profitability - Rina Apriliani; Reza Ashary; Teguh Prakoso; Nekky Rahmiyati; Titiek Rachmawati (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
Finding empirical proof of the effects of Corporate Social Responsibility, Institutional Ownership, Independent Commissioners, Funding Decisions, and Investment Decisions on Profitability is the goal of this study. All of the basic and chemical manufacturing businesses listed on the IDX from 2018 to 2022 served as the study's samples. The total number of samples used in this investigation was 50 samples. In this study, purposive sampling was utilized. Multiple regression analysis is used in this exam using the SPSS. The study's findings indicate that factors including institutional ownership, independent commissioners, funding decisions, and corporate social responsibility (CSR) have little impact on profitability. Profitability, meanwhile, is influenced by investment choices.